Aggregate mutual fund holdings and fund performance - BHOJRAJ, Sanjeev (Institutional Knowledge at Singapore Management University, 2018)
In this paper we examine the differences in aggregate ownership of stocks held by passive equity funds and active equity funds and in the characteristics of stocks held by these funds. We find that holdings of passive funds do not mirror the holdings of active funds. There are systematic differences in the holdings between the two groups with active funds more likely to hold smaller stocks, growth stocks, and stocks with higher momentum, higher turnover and more recent IPOs. We also find evidence that the holdings of passive and active funds have trended closer together over time, consistent with the significant inflows into passive funds across all size groups. These systematic differences in holdings suggest that passive funds do not enjoy an intrinsic advantage in after fee performance over active funds. We find that the relative performance of passive and active funds is sensitive to the period over which returns are measured. We show that this time varying relative performance of active and passive funds could be attributable to style differences in aggregate portfolio holding between the two groups.